Optimal DC Fast Charging Placing And Sizing In Iran Capital (Tehran) - M. Mosstafayi; M. Abedi; Gh.H. Riahy Dehkordi (AUT Journal of Electrical Engineering)
DC fast charging (DCFC) and optimal placing of them is a fundamental factor for the popularization of electric vehicles (EVs). This paper proposes an approach to optimize place and size of charging stations based on genetic algorithm (GA). Target of this method is minimizing cost of conversion of gas stations to charging stations. Another considered issue is minimizing EVs losses to find nearest station to recharge batteries. The introduced model forms a mixed-integer non-linear problem and is solved by binary GA and is adopted for finding the optimal place and size of charging stations in Iran capital (Tehran). This practical study proves that the proposed model and method are feasible. Existing gas stations in Tehran are selected as candidate to be converted as DC fast charging. EVs has been outspread throughout of city based on traffic and trips in each municipal districts. The model developed here can be generalized to data set for any region or city and can be used for governmental decision for constructing charging station infrastructure.